2018
DOI: 10.3390/ijerph15020230
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation Positive Pressure Intervention Effect on Indoor Air Quality in a School Building with Moisture Problems

Abstract: This case study investigates the effects of ventilation intervention on measured and perceived indoor air quality (IAQ) in a repaired school where occupants reported IAQ problems. Occupants’ symptoms were suspected to be related to the impurities leaked indoors through the building envelope. The study’s aim was to determine whether a positive pressure of 5–7 Pa prevents the infiltration of harmful chemical and microbiological agents from structures, thus decreasing symptoms and discomfort. Ventilation interven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Therefore, it is very important to pay attention to the quality of that indoor air, temperature, humidity, and pressure, especially as COPD patients must live in a safe environment, away from any kind of irritants. Based on the outcomes of a wide range of studies [35][36][37][38][39][40][41][42][43][44][45][46][47] that addressed internal environmental conditions, we were able to draw up safe limits for all indoor climate factors. The foundations of internal protection have been translated into a hierarchical tree, as shown in Figure 4.…”
Section: Indoor Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very important to pay attention to the quality of that indoor air, temperature, humidity, and pressure, especially as COPD patients must live in a safe environment, away from any kind of irritants. Based on the outcomes of a wide range of studies [35][36][37][38][39][40][41][42][43][44][45][46][47] that addressed internal environmental conditions, we were able to draw up safe limits for all indoor climate factors. The foundations of internal protection have been translated into a hierarchical tree, as shown in Figure 4.…”
Section: Indoor Rulesmentioning
confidence: 99%
“…The COPD Foundation's Slim Skinny Reference Guide (SSRG) [39] and Excellus BlueCross BlueShield [40] suggested keeping the indoor humidity below 40% and above 30%, respectively, to avoid harmful influences. Indoor pressure has a significant effect on breathing; it has been shown that negative pressure indoors may introduce harmful pollutants [41,42]. Generally, positive air pressure means that the indoor space is supplemented with 5 Pa/0.02 WC of filtered air with respect to the outside atmospheric pressure [43].…”
Section: Indoor Rulesmentioning
confidence: 99%
“…Mycobiota in indoor dust was obtained from the settled dust collected from Classrooms 1 and 2 and the lobby before the ventilation improvement (May 2016) and 10 months after the improvement (March 2017). These mycobiota were characterized in three stages, as described previously [ 18 ]: sampling of dust, rapid toxicity screening of single colonies, and characterization and identification of the fungal isolates.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to viable conidia emitted from potentially pathogenic Trichoderma species, such as T. longibrachiatum and T. citrinoviride , represents an additional health risk [ 14 , 17 ]. Measurement of cultivable conidia from pathogenic and toxigenic fungi in settled dust in schools is an easy method to determine the potential health risk associated with changes in ventilation and fluctuations in indoor air pressure [ 18 ]. House dust is a long-term reservoir of indoor fungi, therefore it is frequently collected to evaluate cumulative exposure and fungal composition [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation